Is a smart sustainable city a marketing-oriented city? - Tibor László BUSKÓ (Smart Cities and Regional Development Journal)
More recently, the instrumentalist approach to the the smart city concept, which emphasises different ICT solutions, is being replaced by a functionalist approach which focuses on the purpose of the smart city. If this purpose is identified with adapting to the needs of current and future generations of citizens, a strong convergence between the concepts of the smart sustainable city and the marketing-oriented city can be predicted in the near future. In my paper I have try to detect the first signs of this convergence process in the Hungarian discourse on the development of smart sustainable cities. Therefore, I empirically analyse the sustainable urban development strategies of the most important Hungarian cities prepared between 2021 and 2024, which are key for the use of EU funds for sustainable urban development. The analysis focuses primarily on the different approaches to the concept of city marketing and the peculiarities of their use, using the methodological tool of content analysis. The results are rather mixed: although the cities analysed almost without exception try to integrate marketing (especially sales communication) into the practice of smart sustainable urban development, the majority of these documents are still not sufficiently customer-oriented. Moreover, the lack of an integrated marketing approach is also a very typical problem, mainly due to the dominance of sectoral marketing limited to tourism or economic development and/or the absence of a management approach. However, in the absence of a correct and complete use of the city marketing concept, there is little chance of really good practices of smart sustainable urban development being established in the near future. The main aim of this paper is to draw the attention of urban policy practitioners and academics to this danger.